METODE CARDIO PULMONARY RESUSCITATION UNTUK MENINGKATKAN SURVIVAL RATES PASIEN POST CARDIAC ARREST - Roifah, Ifa (S1 Keperawatan, 2014)
Abstract Cardiac arrest is the main cause of death in the world, in which the heart does not deliver the blood that can cause brain damage in 4-6 hours and becoming irreversible within 5-10 minutes if not treated right away. Chest compression, to maintain blood circulation, combined with breathing, help to oxygenate the blood, called cardio pulmonary resuscitation, is a major aid should be immediately done when cardiac arrest appear. This research aims to analyze the effect of administering CPR toward the survival rates in post cardiac arrest patient in ICCU of RSUD Sidoarjo. The research design was analytical with case-control approach. The technique of collecting data through secondary data and analyzed with descriptive statistics analysis. The sampling technique used is total sampling so that the number of population and the sample is the same, as much as 8 patients. Results of research conducted on 1-14 may 2014 in ICCU of RSUD Sidoarjo stating that the average survival time of patients that get resuscitation or CPR have higher survival compared with patients who got only 1 cycle. Administering CPR is also influenced by other factors, namely the quality of giving CPR itself, internal factors such as the patients condition or the cause of cardiac arrest companion on a patient, age and gender factors. The research indicates that giving resuscitation (CPR) fast and precise will increase the survival rates of patients with cardiac arrest. Keywords : cardiac arrest, cardio pulmonary resuscitation, survival rates.